The new approach to developing store brand strategy: a case from China. (2016) - Song, Wei; Schein, David D.; Collins, Roger
The significant growth of store brands in grocery retailing has encouraged extensive studies of Western grocery markets, while similar studies of emerging markets like Asia, Africa and Eastern Europe are limited. This qualitative study investigates how a store brand strategy may lead to store loyalty in Chinese grocery sector. The theoretical foundation of the study is derived from various concepts of competitive advantage, including the classic differentiation concept, Hunt's resource-advantage theory and Aaker's brand relevance model. The findings reveal that a new approach that combines brand relevance, differentiation and resource advantage can develop qualitatively differentiated Chinese store brands. The study concludes that the store brands built through such a strategic approach drastically enhance store loyalty in China's retail grocery market. This study provides guidance for Chinese and international retailers who are engaging in Chinese store brand development. The limitations of the study are also presented, together with suggestions for future research.